Application of 3D VSP acquired with DAS and 3C geophones for site characterization and monitoring program design: Preliminary results from Stage 3 of the CO2CRC Otway project - Correa, J.; Pevzner, Roman; Popik, S.; Tertyshnikov, Konstantin; Bona, Andrej; Freifeld, B. (2019)
© 2018 SEG. Distributed Acoustic Sensing (DAS) is a relatively novel technology that is gaining increasing popularity in the seismic industry, particularly as a tool for permanent reservoir monitoring and time-lapse imaging. Recent studies show that DAS can deliver promising results for such applications, presenting satisfactory levels of repeatability and signal-to-noise ratio. However, issues such as high angle dependent sensitivity and high levels of noise still limit certain applications of the method. In this work, we present the preliminary results from a 3D VSP survey acquired using a cemented single-mode fiber-optic cable as a part of the seismic monitoring and characterization effort within CO2CRC Otway Project. We investigate the imaging limitations of a 3D VSP acquired with DAS by analyzing the quality of DAS datasets in relation to offset and angle, as well as assess a migrated line from the DAS VSP datasets.